Efetividade dos direitos humanos: a sociedade civil e os writs constitucionais - Inouye, Giselle Ashitani (2011)
After a long and dark period of dictatorial regime in which rights and guarantees were suppressed, the mobilization of the civil society allowed Brazil s redemocratization. The Constitution of 1988, also kown as the Citizen Constitution, is considered the legal landmark of this process of transition. Civil society is an important vector for the political and social changes. In this context, this paper aims to study the defense of human rights by civil society through the use of constitutional writs as mechanisms to ensure the fullest effectiveness of these rights